Health Center Innovation: Using Ai To Prevent Heart Disease - Musawaris, Rubil; Sutedja, Indrajani (Publikasi Indonesia, 2025)
Throughout the world, the disease most people suffer from is heart disease. Likewise with Indonesia, many Indonesian people have heart disease. The cause of the high death rate from heart disease is still a lack of experts who can treat heart disease well. Apart from that, there is also a low level of public awareness to carry out regular checks on the development of their heart health. Because heart disease is still one of the main causes of death throughout the world and Indonesia, this is a topic to increase public awareness and explore the role of artificial intelligence (AI) in the prevention and early detection of heart disease. We explore what AI can do to prevent and cure heart disease, AI works by performing deep machine learning, and neural network learning and how it can be applied to analyze large data sets to identify risk factors, predict outcomes, and support decisions. clinical decisions. The focus is to leverage AI and improve early predictions for the public, personally providing patient care. In this article, readers can learn about the benefits and limitations of AI in the context of heart disease and emphasize the need for high-quality data in order to obtain appropriate analysis results. Finally, this paper suggests that other researchers carry out further research, such as improving the interpretability of AI models, expanding and searching for multiple data sources, and encouraging collaboration between government, society and medical personnel. The potential of using AI can reduce people's risk of heart disease and AI offers a path to better public health outcomes and more efficient health services to treat it and detect it early.